2013
DOI: 10.1590/s0036-46652013000600007
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Pathogenic Free-Living Amoebae in Some Flood-Affected Areas During 2011 Chiang Mai Flood

Abstract: SUMMARYThe survey was carried out to investigate the presence of potentially pathogenic free-living amoebae (FLA) during flood in Chiang Mai, Thailand in 2011. From different crisis flood areas, seven water samples were collected and tested for the presence of amoebae using culture and molecular methods. By monoxenic culture, FLA were detected from all samples at 37 °C incubation. The FLA growing at 37 °C were morphologically identified as Acanthamoeba spp., Naegleria spp. and some unidentified amoebae. Only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, incidence of AK in developing countries is often related with outdoor activities and risk exposures to dust, soil or water [1]. In Thailand, Acanthamoeba have been isolated from clinical and environmental samples [5,16–19]. Despite its ubiquity in the nature, less than 10 AK cases have been previously reported from Thailand [20], bringing up to the curiosity that the true AK incidence may be underestimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, incidence of AK in developing countries is often related with outdoor activities and risk exposures to dust, soil or water [1]. In Thailand, Acanthamoeba have been isolated from clinical and environmental samples [5,16–19]. Despite its ubiquity in the nature, less than 10 AK cases have been previously reported from Thailand [20], bringing up to the curiosity that the true AK incidence may be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, a sample of corneal re-scraping was subjected to Acanthamoeba culture. Monoxenic culture was performed on a 1.5% non-nutrient agar plate pre-coated with heat-inactivated Escherichia coli as previously described [5]. On the second day of incubation, a clear plaque on the bacteria lawn resulting from bacterial consuming by Acanthamoeba was clearly seen.…”
Section: Case Recordmentioning
confidence: 99%
“…and Acanthamoeba spp. were identified by culture during the flood disaster in Chiang Mai, Thailand [ 35 ]. To date, this is the first report of the direct identification of N .…”
Section: Discussionmentioning
confidence: 99%
“…During flood events, several types of microorganisms are present in the flood water, such as human enteric viruses (Ngaosuwankul et al, 2013), free-living amoebae (Wannasan et al, 2013), and bacteria (Chaturongkasumrit et al, 2013). Contaminated flood water indicated a high risk of health problems.…”
Section: Discussionmentioning
confidence: 99%
“…(Chaturongkasumrit et al, 2013). A study carried out in Chiang Mai, Thailand, in 2011, found that water samples collected from seven flood crisis areas in Chiang Mai were contaminated with free-living amoebae (Wannasan et al, 2013). Flood water samples collected from flood zones in central Thailand, in 2011, were contaminated with human enteric virusesnorovirus (14%), rotavirus (9%), and hepatitis A (7%) (Ngaosuwankul et al, 2013).…”
Section: Introductionmentioning
confidence: 99%